PROPOSED NO SMOKING ORDINANCE IN CRANSTON, RHODE ISLAND. - OLIVERIO,RA (Tufts Archival Research Center, 2007)
Memo from Raymond Oliverio to Roger Mozingo regarding a proposed smoking ban in Cranston, Rhode Island. Discusses success of Lorillard in Cranston. Suggests the Industry Support System be broadened. Summarizes actions taken and people and organizations contacted and involved.